Rapidly spreading mangroves at Port Gawler, South Australia: an update. Issue 2 (17th February 2018) - Cann, J. H.; Jago, J. B.
ABSTRACT: The previously reported rapid spread of mangroves at Port Gawler on the northeastern shore of Gulf St Vincent, South Australia has continued. This is a tidal-dominated coastline where reduced incoming tidal currents have led to increased sedimentation on the tidal flat and the development of an area of samphire and mangroves that have split the tidal flat in two. We predict that the remaining sections of the tidal flat will eventually become a mature mangrove forest, although human activity may delay this process.